Perceptions of Teachers Using AI-Based Tools in English Language Teaching at Elementary Schools - Comodor Leo Fatimina; Muhaimin Abdullah; Him'mawan Adi Nugroho (Pusdikra Publishing, 2026)
This qualitative case study investigates elementary school English teachers’ perceptions of and challenges in integrating Artificial Intelligence (AI)-based tools into English language teaching. Although the rapid development of AI technologies offers new opportunities for enhancing language learning, limited research has focused on how elementary school teachers perceive and experience the use of these tools in classroom practice. Therefore, this study aims to explore teachers’ attitudes toward AI-based tools and to identify the challenges they encounter during implementation. Data were collected from six elementary school English teachers through semi-structured interviews, classroom observations, and document analysis. The data were analyzed using thematic analysis to identify recurring patterns and key themes related to AI integration in English language teaching. The findings indicate that teachers generally perceive AI-based tools as beneficial for increasing student engagement, supporting individualized learning, and improving teaching efficiency. AI tools such as ChatGPT, Google Translate, Canva, and Quizizz were commonly used to assist lesson planning, material development, and interactive learning activities. However, several challenges were also identified, including limited technological infrastructure, insufficient teacher training, students’ over-reliance on AI tools, and concerns related to data privacy and content accuracy. In conclusion, the study highlights that the effective integration of AI in elementary English language teaching requires not only access to technology but also continuous professional development and institutional support. The findings provide practical implications for teachers, school administrators, and policymakers in developing balanced and responsible strategies for AI adoption in primary English language education.